Considering the camp: ambivalent geographies of mobile dwelling. Issue 1 (2nd January 2020) - Collins, Damian; Bates, Laura; Kearns, Robin; Evans, Joshua
Abstract: As code for spaces of mobile dwelling, the camp and its verb "camping" occupy ambivalent territory. For the well-housed, camping out can be a space and time of recreational discretion, while for those living precariously, the camp can offer temporary respite from forced and continual mobility. We argue that notions of camping are defined in part by their opposite: regular, permanent, secure and formal housing. However, not all campers have housing to "return" to. We examine these nuances and tensions with reference to campgrounds in Auckland, New Zealand, which function as sites of tourist accommodation and informal housing. Our survey of eight urban campgrounds reveals that many have become disciplined sites, recalling Agamben's conceptualization of the camp. Drawing on the accounts of managers and campers, we examine the ambivalent geographies of campgrounds through three key narratives: residing, moving and mooring. We focus in particular on the experiences of long-term resident campers, for whom campgrounds offer a sense of home and community, while subjecting them to control and inherent insecurity. In addition, campgrounds themselves have an uncertain foothold in urban space, as they are sought-after for redevelopment. Hence, it is useful to conceptualize campground occupation in terms of mooring – a static site that may be occupied for an indeterminate length of time as part of a longer housing "voyage". At the same time, the fact of long-term residence suggests the emergence of a form of camp space that is not counterpoised with a permanent home elsewhere.